Contribution of Short-Time Occlusion of the Amblyopic Eye to a Passive Dichoptic Video Treatment for Amblyopia beyond the Critical Period - Lauren Sauvan; Natacha Stolowy; Danièle Denis; Frédéric Matonti; Frédéric Chavane; Robert F. Hess; Alexandre Reynaud (Neural Plasticity)
Dichoptic movie viewing has been shown to significantly improve visual acuity in amblyopia in children. Moreover, short-term occlusion of the amblyopic eye can transiently increase its contribution to binocular fusion in adults. In this study, we first asked whether dichoptic movie viewing could improve the visual function of amblyopic subjects beyond the critical period. Secondly, we tested if this effect could be enhanced by short-term monocular occlusion of the amblyopic eye. 17 subjects presenting stable functional amblyopia participated in this study. 10 subjects followed 6 sessions of 1.5 hour of dichoptic movie viewing (nonpatched group), and 7 subjects, prior to each of these sessions, had to wear an occluding patch over the amblyopic eye for two hours (patched group). Best-corrected visual acuity, monocular contrast sensitivity, interocular balance, and stereoacuity were measured before and after the training. For the nonpatched group, mean amblyopic eye visual acuity significantly improved from 0.54 to 0.46 logMAR (p<0.05). For the patched group, mean amblyopic eye visual acuity significantly improved from 0.62 to 0.43 logMAR (p<0.05). Stereoacuity improved significantly when the data of both groups were combined. No significant improvement was observed for the other visual functions tested. Our training procedure combines modern video technologies and recent fundamental findings in human plasticity: (i) long-term plasticity induced by dichoptic movie viewing and (ii) short-term adaptation induced by temporary monocular occlusion. This passive dichoptic movie training approach is shown to significantly improve visual acuity of subjects beyond the critical period. The addition of a short-term monocular occlusion to the dichoptic training shows promising trends but was not significant for the sample size used here. The passive movie approach combined with interocular contrast balancing even over such a short period as 2 weeks has potential as a clinical therapy to treat amblyopia in older children and adults.